Analysis of major factors shaping the automotive industry in the long term, including ageing population, urbanization trend, and e-commerce business in Europe - Nikolayenko, Viktoriya (2015)
In recent decades a number of new trends have evolved. Ageing population, increased urbanization, growth of technology, e-commerce expansion, changes in social views, and other developments have significant influence on the conventional industries. In this rapidly changing environment, businesses find themselves under pressure when analyzing market trends and planning their industry activities. Adam Opel AG, the automotive company, provided the author the opportunity to conduct research on the basis of a dissertation internship, addressing three main questions that have arisen within the industry forecasting team of the long-term planning department. “Who will buy new cars?” This question addresses major demographic challenges in Europe such as ageing population, immigration, social transformation and other. The author investigates how these tendencies impact vehicle sales and vehicle design. “What car and technology does the new customer want?” Today’s increased population density has led to serious congestion and environmental problems. The author looks into how European governments address these matters, encouraging the development of the electric vehicle market, and how European minds respond to these challenges. “What is the risk and value from new automotive business models?” New businesses appeared in a result of population density increase, e-commerce expansion, and new European minds that support collaborative consumption. The author analyzes how automotive companies can join and benefit from these new businesses. As a result of the research, the author advises on several aspects: forecasted vehicle demand, changes in vehicle car design and technology, and suggests several models for joining new businesses.